(untitled) (Modern education and development, 2025)
This article explores the significance of grammar within the field of linguistics, emphasizing its structural and functional roles in language analysis. It reviews major theoretical approaches, compares traditional and modern perspectives, and analyzes grammar’s application in language teaching and computational linguistics. The study concludes that grammar remains central to linguistic theory and practice. Grammar serves as the backbone of linguistic analysis, providing the structural framework for understanding language organization and use. This article examines the multifaceted role of grammar in linguistics by exploring its theoretical foundations, key components, and practical applications. It evaluates prominent grammatical models including generative, functional, and structural grammars, and investigates how grammatical principles inform language acquisition, teaching methodologies, and computational language processing. Furthermore, it discusses the relevance of descriptive versus prescriptive approaches to grammar, offering insights into linguistic diversity and social context. By integrating perspectives from cognitive science, sociolinguistics, and applied linguistics, the study underscores grammar’s dynamic and evolving nature. The findings reveal that grammar is not merely a set of rigid rules but a flexible system shaped by cognition, culture, and communication needs. The article concludes by emphasizing the continued importance of grammar in both theoretical inquiry and applied linguistic practices.